2019
DOI: 10.1158/0008-5472.can-19-0244
|View full text |Cite
|
Sign up to set email alerts
|

Src-Dependent DBL Family Members Drive Resistance to Vemurafenib in Human Melanoma

Abstract: The use of selective BRAF inhibitors (BRAFi) has produced remarkable outcomes for patients with advanced cutaneous melanoma harboring a BRAF V600E mutation. Unfortunately, the majority of patients eventually develop drug-resistant disease. We employed a genetic screening approach to identify gain-of-function mechanisms of BRAFi resistance in two independent melanoma cell lines. Our screens identified both known and unappreciated drivers of BRAFi resistance, including multiple members of the DBL family. Mechani… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 47 publications
(68 reference statements)
0
33
0
Order By: Relevance
“…The transcriptomic signature of ibrutinib-treated cells is similar to that of cells treated with SRC family kinase inhibitors. Other studies have also identified a role for SFKs in BRAFi resistance (Girotti, Pedersen et al 2013, Fallahi-Sichani, Becker et al 2017, Feddersen, Schillo et al 2019, further supporting the idea that off-target anti-SFK activity of potential melanoma therapeutics may be mechanistically important. One study in particular characterized a novel dual RAF/SRC inhibitor which retains activity against melanoma tumors which had previously developed resistance to dabrafenib/trametinib therapy (Girotti, Lopes et al 2015).…”
Section: Discussionmentioning
confidence: 79%
“…The transcriptomic signature of ibrutinib-treated cells is similar to that of cells treated with SRC family kinase inhibitors. Other studies have also identified a role for SFKs in BRAFi resistance (Girotti, Pedersen et al 2013, Fallahi-Sichani, Becker et al 2017, Feddersen, Schillo et al 2019, further supporting the idea that off-target anti-SFK activity of potential melanoma therapeutics may be mechanistically important. One study in particular characterized a novel dual RAF/SRC inhibitor which retains activity against melanoma tumors which had previously developed resistance to dabrafenib/trametinib therapy (Girotti, Lopes et al 2015).…”
Section: Discussionmentioning
confidence: 79%
“…A range of genetic mutations have been identified as causing acquired BRAF resistance (recently reviewed by Tian and Guo and summarized in Table 1 ) [ 11 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ...…”
Section: Resultsmentioning
confidence: 99%
“…The PB system was used to identify mechanisms of resistance to an Mdm2 inhibitor in PB-accelerated tumors of various types passaged as allografts [134]. Although the following studies were not carried out in vivo, but rather in cell lines, it is worth noting that transposon mutagenesis has been successfully used to screen for cancer cell drug resistance in several reports [134,135]. Taken together, these studies suggest that cancer evolution in response to the selective pressures of therapy can be usefully explored using transposon mutagenesis.…”
Section: Therapy Resistancementioning
confidence: 99%